2016
DOI: 10.1136/neurintsurg-2016-012633
|View full text |Cite
|
Sign up to set email alerts
|

Too good to intervene? Thrombectomy for large vessel occlusion strokes with minimal symptoms: an intention-to-treat analysis

Abstract: IntroductionThe minimal stroke severity justifying endovascular intervention remains elusive; however, a significant proportion of patients presenting with large vessel occlusion (LVO) and mild symptoms subsequently decline and face poor outcomes.ObjectiveTo evaluate our experience with these patients by comparing best medical therapy with thrombectomy in an intention-to-treat analysis.MethodsAnalysis of prospectively collected data of all consecutive patients with National Institutes of Health Stroke Scale (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 16 publications
8
100
5
Order By: Relevance
“…These findings complement our prior pilot prospective intention-to-treat analysis of thrombectomy versus medical management for patients with an NIHSS score ≤5, which found a statistically significant discharge NIHSS score shift favoring ET-managed patients (-2.5 vs. 0, p = 0.01) and numerically higher rates of good outcomes [15]. …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings complement our prior pilot prospective intention-to-treat analysis of thrombectomy versus medical management for patients with an NIHSS score ≤5, which found a statistically significant discharge NIHSS score shift favoring ET-managed patients (-2.5 vs. 0, p = 0.01) and numerically higher rates of good outcomes [15]. …”
Section: Discussionsupporting
confidence: 74%
“…While historically thought to be a relatively benign condition, more recent data have shown that even these putatively minor strokes, if untreated, lead to higher rates of early neurologic decline, requiring rescue thrombectomy in up to 40% of patients, as well as lower rates of favorable clinical outcomes and independence, compared to patients receiving thrombolysis, ET, or both, with the greatest trend towards poor outcomes amongst untreated patients with an NIHSS score of 5-7 [5,8,15,17]. …”
Section: Discussionmentioning
confidence: 99%
“…The main limitation is the absence of a control group undergoing optimal medical management. A recent small case-control study suggested that MT may lead to a shift towards a lower NIHSS at discharge than due to medical management alone [29]. These data, focusing on MT in minor-to-mild AIS patients, point to the importance of conducting future randomized studies comparing optimal medical management alone to optimal medical management combined with MT in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whether patients with LVOS presenting with low NIHSS benefit from ET remains controversial. 1,19 Moreover, LVOS patients with lower clinical severities theoretically have better collateral flow, which is associated with better natural history, higher chances of response to IVT, and potentially a longer treatment window for ET. 20 As such, it is reasonable if not more logical that most patients with LVOS and low NIHSS would be first evaluated at a closer PSC/ ASRH to be assessed for IVT and undergo neurovascular imaging before the transportation to a more distant CSC.…”
Section: Discussionmentioning
confidence: 99%